Arbitration and alternative dispute resolution : how to settle international business disputes : with supplement on Indian Arbitration Law - Kwatra, G. K.; Indian Council of Arbitration; International Trade Centre UNCTAD/WTO. (New Delhi : Indian Council of Arbitration, 2005)
With the acceleration of cross-border trade, business operators are exposed to new partners, countries, cultures and trade practices. Business dealings naturally give rise to disputes. This publication sets out the different alternatives to State proceedings that may be used to prevent or settle business disputes in an international context.
1. Types of international business disputes and possible remedies --2. Preventing commercial disputes --3. Resolving commercial disputes and differences --4. Types of international commercial arbitration --5. Constituting the arbitral tribunal --6. Powers, duties and judisdiction of the arbitral tribunal --7. Conduct of arbitration proceedings --8. Applicable law --9. The arbitral award --10. Recongnition, enforcement and challenge of arbitral awards --11. The arbitration costs --12. Drafting an arbitration clause: preliminary questions --13. Contents of an arbitration clause --14. Pathological clauses (or clauses to avoid at all costs) --15. Recommended drafting for arbitration agreements --16. Selected model clauses.
'International Trade Centre UNCTAD/CNUCED, WTO/OMC, ICA.'
Includes bibliographical references and index.
Keywords: International commercial arbitration; Arbitration and award -- India